2022
DOI: 10.3390/land11081336
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Ecosystem Service Trade-Offs and Their Response to Landscape Patterns at Different Scales in an Agricultural Basin in Central China

Abstract: Identifying relationships among multiple ecosystem services (ESs) at different scales and the factors affecting such relationships is the foundation for sustainable ecosystem management. A case study was conducted in the Sihu Lake Basin, an agricultural basin in Central China, to examine the interactions among ESs across different scales and the responses to landscape pattern changes (2000–2020). The results indicate that (1) agricultural land and wetlands were converted into construction land and gradually de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…While correlation analysis can calculate the trade-offs or synergies among ESs, it can hide the spatial heterogeneity of ES's relationships [68,69]. For example, the correlation results showed that 10 pairs of ES relationships between the five ESs types were robust across scales (Figure 3) mainly due to land-use consistency [13,28,66]. However, the spatial overlay results showed that changing the scale can enhance, weaken, or even reverse the interaction between ESs (Figure 5), which suggested that the relationship of ESs changed both in direction and strength across scales [70,71].…”
Section: Multiscale Characteristics Of Ess Trade-offs and Synergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While correlation analysis can calculate the trade-offs or synergies among ESs, it can hide the spatial heterogeneity of ES's relationships [68,69]. For example, the correlation results showed that 10 pairs of ES relationships between the five ESs types were robust across scales (Figure 3) mainly due to land-use consistency [13,28,66]. However, the spatial overlay results showed that changing the scale can enhance, weaken, or even reverse the interaction between ESs (Figure 5), which suggested that the relationship of ESs changed both in direction and strength across scales [70,71].…”
Section: Multiscale Characteristics Of Ess Trade-offs and Synergiesmentioning
confidence: 99%
“…Scale effects cannot be ignored when analyzing the relationship between landscape patterns and ecosystems because landscape patterns are scale-dependent and TOSs are spatially heterogeneous [11,12]. Therefore, a multiscale analysis of the effects of landscape patterns on TOSs is essential for ecological management and decision-making [13].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Índice de Relación Perímetro-Area (PAFRAC), ( 2 Esta metodología fue desarrollada por los investigadores Mcgarigal et al (2002), quienes propusieron una serie de índices de paisaje para medir la conectividad y fragmentación del paisaje. El IBP se ha utilizado en numerosos estudios para evaluar la biodiversidad del paisaje y su relación con diferentes variables, como la intensificación agrícola (Li et al, 2022) o la urbanización (Kuang et al, 2021).…”
Section: íNdice De Biodiversidad Del Paisajeunclassified